Coix Seed Oil Alleviates DSS-Induced Ulcerative Colitis via Intestinal Barrier Repair and Ferroptosis Regulation - Zeng YX; Li NR; Deng BY; Gu YF; Lu SF; Liu Y (Journal of Inflammation Research)
Yi-Xuan Zeng,* Ni-Ren Li,* Bing-Ying Deng,* Yu-Feng Gu, Si-Fan Lu, Yi Liu Traditional Chinese Pharmacological Laboratory, Guangdong Provincial Key Laboratory of Chinese Medicine Pharmaceutics, Guangdong Basic Research Center of Excellence for Integrated Traditional and Western Medicine for Qingzhi Diseases, School of Traditional Chinese Medicine, Southern Medical University, Guangzhou, 510515, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Liu, Email liuyi099@163.comBackground: Ulcerative colitis is a chronic intestinal disease linked to intestinal barrier damage, ferroptosis and dysbiosis. Coix lacryma-jobi is a natural food with food-medicine homology, whose seed-derived oil (Coix seed oil, CSO) has been shown anti-inflammatory activity in vitro. Here, the effects and mechanisms of CSO on ulcerative colitis (UC) in vivo are systematically investigated.Methods: Firstly, the UC mice was replicated by 3% DSS, and assessed the efficacy of CSO by observing the fecal occult blood, colon length, DAI score and pathological histomorphological changes of colon tissues. The anti-inflammatory and barrier-protective effects of CSO were observed by AB staining and qRT-PCR. Secondly, the biological targets of CSO were obtained from TCMSP database and Swiss Target Prediction database, ferroptosis targets were downloaded from FerrDb platform, and UC-related disease targets were obtained from GEO database, and the intersection of the above three was taken to obtain “CSO-UC-Ferroptosis” intersection targets, which were analysed by GO and KEGG enrichment, GSEA analysis, and immune cell infiltration and validation. Finally, the core genes of “CSO-UC-Ferroptosis” were molecular docking with the potential active components of CSO. In order to further verify the effect of CSO on ferroptosis, the GPX4 agonist RSL-3 was used to stimulate mice in vivo, and the levels of Iron, MDA and SOD were measured, and immunohistochemistry was used to detect the effects of tight junction proteins and the “CSO-UC-Ferroptosis” core protein in mice. Besides, the effect of CSO was further evaluated by observing the intercellular junctions of the colon tissues of each group under electron microscope. In addition, 16sRNA sequencing was performed on the intestinal contents of the mice to observe the effects of CSO on the intestinal flora of UC mice.Results: CSO improved physiological parameters, reduced inflammation response and intestinal barrier damage, regulated ferroptosis, and restored gut microbiota balance in UC mice. Bioinformatics results showed that G6PD, ABCC1 were core targets at the intersection of CSO, UC and ferroptosis, which also demonstrated the similar expression of the core genes in DSS-induced UC mice models in vivo.Conclusion: Our findings demonstrate for the first time that CSO ameliorated UC by regulating intestinal barrier damage, ferroptosis and the gut microbiota in DSS-induced mice, suggesting that CSO as a promising candidate for UC treatment and warranting further investigation.Keywords: coix seed oil, ulcerative colitis, intestinal barrier, ferroptosis, network pharmacology, gut microbiota